THE CHARACTER BUILDING CONCEPT FOR TEENAGERS IN THE QUR’AN; ANALYTICAL STUDY OF MUSA AS STORY - Binti Ramli, Angraini; Elatrash, Radwan Jamal (Borneo International Journal of Islamic Studies, 2020)
The moral decadency and its degradation specifically in teenagers considered as worldwide problem nowadays. Many other cases occurred as the result of ignorance from parents, community and all those who are responsible in their upbringing and building their character such as harassment, bullying cases between teenagers and low ethic association between them. Being captivated by gender stereotypes leads to inequality and inbalance which resulted low and poor character. The duty of Prophet Muhammad saw for being sent down to people in beautifying their morals is in harmony with character building concepts mentioned in al-Qur?an. This paper analyses interactions between Musa As and the daughters of Prophet Syu?aib from surah al-Qasas which told about how to interact between genders and the balance personalities and character they owned. This research results that the perfections of Akhl?q and morals which is a symbolic of the beauty of akhl?qalso the most important point in obtaining a high quality of life.